A Review Paper on Performance Management - Mohanty, Sasmita (International Journal of Psychosocial Rehabilitation, 2019)
The main objective in managing human resources is to make optimal use of human resources so that goals can be met in a very effective and efficient manner. For this purpose it is very important to manage employee performance as a whole. This feature takes care of the performance management. Performance management preserves, improves and motivates working people to deliver better outcomes. The company that gives better results will succeed, stabilize, expand and excel in success in the present competitive situation. This helps in reaching HRM's targets. Activities include performance management. To ensure that targets are met consistently in an efficient and effective manner. Performance management may concentrate on organizational quality, a team, Product or service building processes, staff, etc. For most organizations, performance reviews are used to support decisions relating to training and career development, compensation, transfers, promotions, and termination of employment or reduction in force. Generally speaking, the performance review process involves setting clear and specific performance expectations for each employee and offering regular informal or formal input on performance of employees according to those stated objectives. However, recent trends include a less formalized process that focuses more on feedback and coaching, rather than a time-consuming paper trail.